A Theoretical and Empirical Analysis of the Implications of Aging Population on Macroeconomic Variables - Gevorgyan, Kristine (2022)
The dissertation thesis is a collection of three academic articles on the topic of aging population and its effect on certain macroeconomic variables. It explains theoretically and empirically the relationship between demographics and house prices, real interest rate, and current account balance. The combined evidence of the research shows that demographic shifts have a significant impact on these variables. The goal of the dissertation thesis is to provide a unied framework for understanding and analyzing the role of demographics, and especially aging population on some key macroeconomic variables. At first, the dissertation looks at house price movements due to demographic shifts. Naturally, the dissertation next focuses on two closely related subjects, the real interest rates and the current account imbalance. The first paper tests the idea that major demographic shifts can aeffect house prices. It first builds an overlapping generation model and analytically solves for the equilibrium price of the asset. The model predicts that economies with a higher fraction of old people in the overall population have lower house prices. It then empirically tests this hypothesis using data on house prices and demographic variables from the OECD. The main finding is that if population growth increases by one percentage point house price growth increases by 1.4 percentage points. The second paper asks if demographic changes affect the real interest rates? It shows both theoretically and empirically that an increase in the population growth raises the real interest rate. It solves analytically for the equilibrium real interest rate using a three-period overlapping generation model. The model confirms that when an economy is experiencing a higher share of younger people, the real interest rate increases. The paper empirically tests this hypothesis using cross-country regressions with data on the real interest rates and demographic variables from the OECD.